Neurofibrosarcoma: case series in south-south Nigeria - Asuquo, Maurice; Nwagbara, Victor; Nnoli, Martin; Ashindoitiang, John; Ugbem, Theophilus; Akpan, Samuel (International Journal of Medicine, 2017)
Neurofibrosarcoma is a malignancy that occurs more frequently in patients with neurofibromatosis- 1 (NF- 1) and rarely may arise independently. This is a presentation of 3 consecutive patients with histologic diagnosis of neurofibrosarcoma who presented to the University of Calabar Teaching Hospital, Calabar from 2011-2013. Two patients presented were associated with NF-1 and were a decade younger than the one without NF-1. Late presentation and poor follow up were notable underlying factors. Long term follow up of patients with NF -1 for early diagnosis and adequate treatment will improve outcome.